2016
DOI: 10.4103/0366-6999.182828
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Immunosuppressive Protocol of Liver Transplant Recipient Should be Made Based on Splenic Function Status

Abstract: Background:Lymphocyte subsets play important roles in rejection in liver transplant recipients, and the effect of splenic function on these roles remains unknown. The aim of this study was to explore the feasibility to adjust immunosuppressive agents based on splenic function status through detecting the lymphocyte subsets in liver transplant recipients.Methods:The lymphocyte subsets of 49 liver transplant recipients were assessed in the 309th Hospital of Chinese People's Liberation Army between June 2014 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Thus, the recipient-related valuables, for example, age, gender, diagnosis, previous abdominal surgery, body weight, graft-to-recipient weight ratio (GRWR, %), Child-Pugh classification, and model for end-stage liver disease (MELD) score calculated with the most recent blood test results available before LDLT, were all included. [ 1 2 6 24 25 26 27 28 29 ] MELD score = 9.6 × Ln creatinine (mg/dl) + 3.8 × Ln bilirubin (mg/dl) + 11.2 × Ln (INR) + 6.4 × etiology (biliary or alcoholic cirrhosis was 0, otherwise 1). [ 30 ] Donor-related variables such as donor age, gender, and graft weight were also collected.…”
Section: Ethodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the recipient-related valuables, for example, age, gender, diagnosis, previous abdominal surgery, body weight, graft-to-recipient weight ratio (GRWR, %), Child-Pugh classification, and model for end-stage liver disease (MELD) score calculated with the most recent blood test results available before LDLT, were all included. [ 1 2 6 24 25 26 27 28 29 ] MELD score = 9.6 × Ln creatinine (mg/dl) + 3.8 × Ln bilirubin (mg/dl) + 11.2 × Ln (INR) + 6.4 × etiology (biliary or alcoholic cirrhosis was 0, otherwise 1). [ 30 ] Donor-related variables such as donor age, gender, and graft weight were also collected.…”
Section: Ethodsmentioning
confidence: 99%
“…However, a remaining challenge for the transplantation community is a relative scarcity of deceased donor graft. [ 1 2 ] Therefore, in addition to deceased donor LT (DDLT), living donor LT (LDLT) has emerged as a solution to the lack of deceased donor organs and has effectively expanded the donor pool. [ 2 ] Although it is a complicated surgical procedure that deals with the right or left lobe and dramatic physiological changes resulting from liver regeneration,[ 3 ] a recent meta-analysis revealed that LDLT was associated with a higher rate of surgical complications but with no significant difference in perioperative mortality compared to DDLT.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, IS therapy for LTx patients should be tailored to the immune status of the individual patient. [ 1 ] Biliary complications (BC), including biliary strictures with cholangitis, are the most common complications after LTx. However, the immunological characteristics especially T cell-mediated immunity of these patients are unknown yet.…”
mentioning
confidence: 99%